2018
DOI: 10.1111/bld.12253
|View full text |Cite
|
Sign up to set email alerts
|

A dialogic approach to working inclusively in a Research Reference Committee

Abstract: Accessible summary People with intellectual disability do not often take part in research. We wanted to include people with intellectual disability on our research committee. We worked with two people with intellectual disability to help with their roles on the research committee. We talk about some ideas that made this work well. Two people with intellectual disability share their ideas on being a part of a Research Reference Committee. Abstract This paper reports the use of a dialogic approach to working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Just as other researchers (e.g., Björnsdóttir and Svensdóttir 2008;Lloyd et al 2019), we also found it challenging to empower co-researchers with intellectual disabilities to exercise control over the research process and the reporting of findings. To ensure that control, we sought to comply with the interests and choices of co-researchers with intellectual disabilities (regarding research problems, research participants, and research location).…”
Section: Overcoming Challengesmentioning
confidence: 76%
See 2 more Smart Citations
“…Just as other researchers (e.g., Björnsdóttir and Svensdóttir 2008;Lloyd et al 2019), we also found it challenging to empower co-researchers with intellectual disabilities to exercise control over the research process and the reporting of findings. To ensure that control, we sought to comply with the interests and choices of co-researchers with intellectual disabilities (regarding research problems, research participants, and research location).…”
Section: Overcoming Challengesmentioning
confidence: 76%
“…Inclusive research may be an answer to the social exclusion experienced by such individuals and the lack of their full participation in different spheres of life (Kramer et al 2011). It has been noted that this type of research enables persons with intellectual disabilities to be empowered, to step out of the role of research subjects, and to assume the valued social roles of leaders and research experts (Walmsley 2001;Lloyd et al 2019;Aubrecht et al 2021). By being both research participants and co-researchers, persons with intellectual disabilities feel valued and included, experience equality, and improve their selfesteem.…”
Section: Benefits and Challenges Of Inclusive Researchmentioning
confidence: 99%
See 1 more Smart Citation